The Role and Efficacy of Clozapine Treatment in Early-Onset and Very Early-Onset Schizophrenia Cases: Discussion of Five Cases - Percinel, Ipek; Yazici, Kemal Utku; Erermis, Hatice Serpil; Ozbaran, Burcu; Kose, Sezen Gokcen; Zemla, Joanna; Idris, Bulent (Kure Iletisim Grubu A S, 2015)
Schizophrenia is a serious mental disorder emerging at an early age, characterized by significant breakdowns in thought, perception and behavioral processes and withdrawal from human relationships. Psychopharmacologic and psychosocial approaches should be combined for the treatment of schizophrenia. Although the effects and side effects of both typical and atypical antipsychotics have been studied in adult patients in detail, studies in child and adolescent age groups are inadequate. Clozapine is a prototype of atypical antipsychotics and the first antipsychotic to be defined as atypical. Clozapine is often effective in cases in which typical and other atypical antipsychotics fail, and is accepted as the gold standard in the treatment of schizophrenia. In this paper, the effects and side effects of clozapine in five adolescent cases diagnosed with schizophrenia are discussed. Four of these cases showed that clozapine is effective in adolescent schizophrenia. While the four cases showing good responses to the treatment tolerated clozapine well, the other case (case 4) showed an apparent decreasing trend in neutrophil count a short while after starting the treatment and his medication was stopped at the request of his parents.
Keywords: Adolescent; adverse effect; child; clozapine; early-onset schizophrenia; treatment; psychopharmacology